The Comet assay for detection of DNA damage in canine sperm. (13th August 2017) - Pereira, AF; Borges, P; Fontbonne, A; Cardoso, L; Gaivão, I; Martins‐Bessa, A
Contents: Sperm DNA integrity is a fundamental prerequisite in fertilization and embryo development. Among DNA integrity tests, the Comet assay is an accurate and sensitive test for the detection of sperm oxidative damage. The aim of this work was to evaluate sperm oxidative damage using the Comet assay and to study the correlation between Comet and routine assays for the evaluation of semen quality. Dogs were divided in two groups: group A (n = 6), comprising dogs with abnormal spermiogram, that is astheno‐, terato‐ or oligoasthenoteratozoospermic (OAT); and group B (n = 8), comprising normospermic dogs. The distribution of sperm oxidative damage was significantly different between the two groups ( p = .001): group A—median: 31.55%, interquartile range (IQR): 30.18–38.01; group B—median: 0.90%, IQR: 0.65–1.96. The correlation between oxidative damage and abnormal morphology was high ( r = .846; p < .001). There was a negative correlation between progressive motility and oxidative damage ( r = −.792; p = .001). Basal and oxidative DNA damage of spermatozoa are increased in dogs with non‐normospermic semen. In conclusion, and considering the elevated correlation with classical tests of sperm quality, the Comet assay has ample potential for clinical and research purposes in dogs.